Doações, logística reversa e economia circular de medicamentos - Bertolo, Rubem João (Universidade do Vale do Rio dos Sinos, 2019)
The Pharmaceutical Supply Chain (PSC) is complex. It presentes a structure of multiple actors and echelons, and intensively invests in Research and Development for new products launching. Nevertheless, PSC faces problems of demand planning, transportation, distribution, and storage that cause undesirable effects for its reverse flows, that are precariously managed. One of these effects is the generation of large amounts of not utilize dor expired medicines, that end misvalued and discharged in incorrect form, causing unwanted environmental impacts. This research has the aim of identify, classify, and describe, in the academic literature the reverse flows of end-of use medicines (EOU-M), those that can still be valuated and back to one ore more cycle of use, and the end-of-life medicines (EOL-M), already expired, and assess the environmental, economic, and social impacts of these reverse flows, in a case study. The research did not follow a linear planning, because the case study was carried out in two not subsequente phases. In the initial phase, it was performed a data collection about environmental and economic impacts of a municipal program of medicines collection and dispensation. Once verified that the municipality absorves the costs of the reverse flows in order to correctly address expired medicines and, at the same time, generates environmental gains, a bibliographic review was performed. With this review, 122 studies has enabled to classify the reverse flows of medicines as Donations, Reverse Logistics (RL), and Circular Economy (CE). A new phase of the case study was the carried out, and valuable information was gathered on the socioeconomic impacts of the program. The research data were reviewed, and it was achieved that the municipal program performs RL of EOL medicines, and CE of EOU medicines through dispensation. It is recommended the deepening of the research to the investigation of the alternatives of reverse flows that generate not only environmental and socioeconomic returns, but economic returns as well, for th involved agents.
Keywords: Fluxos reversos; Medicamentos fim de uso; Medicamentos fim de vida; Logística reversa; Economia circular; Reverse flows; End-of-use medicines; End-of-life medicines; Reverse logistics; Circular economy; ACCNPQ::Engenharias::Engenharia de Produção